2019
DOI: 10.1186/s12885-019-5488-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 18F-FDG PET/CT in the diagnosis and staging of osteosarcoma: a meta-analysis of 26 studies

Abstract: Background Multiple trials have attempted to assess the diagnostic value of 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) in osteosarcoma with results remaining inconclusive. This study aims to investigate the effectiveness of 18 F-FDG PET and PET/CT in the diagnosis, staging, recurrence and metastasis formation observations of osteosarcoma through systematic review follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 48 publications
2
25
0
1
Order By: Relevance
“…SUVmax, MTV, and TLG have been previously demonstrated as strong predictors of sarcoma cell proliferation and disease progression [ 17 , 18 ]. Several studies have claimed that SUVmax and its retention index could both be used to differentiate between benign and malignant soft tissue or bone lesions [ 19 , 20 ]. Nonetheless, SUVmax is not a precise indicator of the global metabolic activity of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…SUVmax, MTV, and TLG have been previously demonstrated as strong predictors of sarcoma cell proliferation and disease progression [ 17 , 18 ]. Several studies have claimed that SUVmax and its retention index could both be used to differentiate between benign and malignant soft tissue or bone lesions [ 19 , 20 ]. Nonetheless, SUVmax is not a precise indicator of the global metabolic activity of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…24 Recently, 18 F-fluorodeoxy-D-glucose positron emission tomography ( 18 F-FDG PET) and positron emission tomography with computed tomography (PET CT) has emerged as a useful investigation to identify skeletal lesions. 24 A meta-analysis by Liu et al demonstrated a sensitivity of 93% and specificity of 97% for 18 F-FDG PET and PET CT. 25 While these findings are interesting, there are numerous shortcomings to this study which need to be considered. First, the small sample size makes any definitive recommendation in this regard impossible.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, we assessed the usefulness of 18 [17,19]. Several studies have claimed that SUVmax and its retention index could both be used to differentiate between benign and malignant soft tissue or bone lesions [20,21]. Nonetheless, SUVmax is not a precise indicator of the global metabolic activity of tumors.…”
Section: Discussionmentioning
confidence: 99%